Workers' Decisions to Disclose a Mental Health Issue to Managers and the Consequences - Dewa, Carolyn S.; van Weeghel, Jaap; Joosen, Margot C. W.; Gronholm, Petra C.; Brouwers, Evelien P. M. (Frontiers in Psychiatry, 2021)
Background: Stigma can be a barrier to accessing effective interventions and work accommodations for mental illnesses. Fear of stigma’s concomitant prejudice and discrimination can inhibit workers from asking for help. Thus, it may be important to develop effective interventions addressing workplace stigma. To identify important targets for these interventions, this study addresses three questions: (1) what proportion of workers experiencing mental health issues disclosed their mental health issue to their managers, (2) what factors did they identify as contributing to their disclosure decisions, and (3) what were the consequences of their decisions? Methods: The dataset is comprised of responses from respondents who were randomly drawn from a nationally representative sample of working Dutch adults who completed a web-based survey in February 2018. Respondents indicating they either had or have mental health issues were asked three sets of questions focusing on: (1) Did you disclose your mental health issue to you manager? (2) For what reasons did you disclose/not disclose the issue? (3) What were the consequences of your disclosure decision? Results: About 73% of respondents with lived experience with mental health issues told their managers about their mental health issue. The structure of the survey questions identified four groups of workers who either: (1) disclosed and had a positive experience (64.2%), (2) disclosed and had a negative experience (9.0%), (3) did not disclose and had a positive experience (22.6%), or (4) did not disclose and had a negative experience (4.2%). Conclusion: Our results reflect workers’ diverse preferences for disclosing their mental health issues to their managers. Understanding both the factors that contributed to the decision to disclose and the consequences of disclosure decisions could help to better target workplace educational programs and interventions to address workplace stigma. Our findings suggest that addressing workplace stigma may not be as straightforward as requiring all employees to receive anti-stigma education. Rather, education should support workers to make the appropriate disclosure decision based on their workplace contexts. Future research is needed to understand the optimal ways for workers struggling with mental health issues to ask and receive help if they need it.